Digital distractions and employee motivation: the power of internal communication - Jeji Muhamad Najib; Ginta Ginting; Tengku Amir Ramly (Insight Management Journal, 2026)
This study aims to understand how cyberloafing and boss phubbing affect work motivation through internal communication as a mediating variable. This study uses a quantitative approach using a path analysis model. The population consists of ASN employees in the Government Office in Tarakan City, North Kalimantan, with a sample of 139 respondents. The analysis technique uses the SmartPLS version 4.0 approach. The results of the study proved that cyberloafing had a significant influence on internal communication. Boss phubbing had a significant influence on internal communication. Cyberloafing had a significant effect on employee work motivation. Boss phubbing had no significant effect on employee work motivation. Internal communication had a significant influence on employee work motivation. Internal communication mediates between cyberloafing on employee work motivation and internal communication mediates between boss phubbing on employee work motivation. Further research recommendations are to expand the research dimension by considering generational variations, in order to specifically explore the differences in views between Generation X, Generation Y, and Generation Z workers regarding this digital anomaly phenomenon.